The Principle of Economy” and the Issues of Diachronic Phonemics - PETROSYAN, VARDAN (Bulletin of Yerevan University B: Philology, 2021)
A. Martine’s Book “The Principle of Economy in the Phonetic Changes” is one of the fundamental works of diachronic phonemics. According to “The Principle of Economy in the Phonetic Changes” the phonetic/phonemic changes occurring in the language are conditioned by the communication momentum in the process of speaking and the resistance of human anatomy organs to them. This is a phenomenon, which J. Tsipf had formulated as a law of “minimal effort”. Although in A. Martine’sconcept the main functives (series, row, correlation) refer to the paradigm (system), but their function becomes a reality in the flow of speech (syntagm). Accordingly, it is not correct to claim that A. Martine’s “theory of economy” is constructed exceptionally with the counting of systematic data. Although he has treated the notions of “phonetic laws” and linguistic similarities with stipulation and tried to build an open theoretical system which will take into consideration not only the famous facts, but also will leave room for observations, his system is also not devoid of the trend of universality which should be considered quite natural. Being very well-structured “The Theory of Economy” is, however, not devoid of some contemplation of mind.
Keywords: Diachronic Phonemics, “the Principle of Economy”, a law of “minimal effort”, series, row, correlation, opposition